Vilāyatac̃ī bātamīpatrẽ - Keḷakara, Narasĩha Cintāmaṇa, 1872-1947 (SAMP early 20th-century Indian books project ;, 1922)
Newsletters on miscellaneous topics of Great Britain contributed by the author, during his stay in London as member of the deputation of the Home Rule League.